Inequality trends and dynamics in India: The bird's-eye and the granular perspectives - Hai-Anh H. Dang; Peter Lanjouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
India today is achieving per capita growth rates that are historically unprecedented. Poverty reduction has also accelerated. There is concern, however, that this growth is being accompanied by rising inequality. We report on a research project that examines inequality trends and dynamics at the all-India level over three decades up to 2011/12 and contrasts these with evidence at the level of the village, or the urban block. We further unpack inequality to explore dynamics in terms of the movement of people within the income distribution over time. The assessment of mobility is informed both by evidence at the very local level and by aggregate, national-level, trends. Close attention is paid to the circumstances and fortunes of specific population groups. Finally, the study attempts to encapsulate these horizontal inequalities into a measure of inequality of opportunity as captured by inter-generational mobility in education outcomes.
Keywords: D31; I31; O15; R13; 330; inequality; decomposition; welfare dynamics; intra- and inter-generational mobility; India